2017
DOI: 10.3892/or.2017.6144
|View full text |Cite|
|
Sign up to set email alerts
|

miR-29a inhibits human retinoblastoma progression by targeting STAT3

Abstract: Retinoblastoma (RB) is the most common malignancy that occurs during childhood. Growing evidence supports a crucial role for microRNAs (miRNAs) in regulating the initiation and progression of RB. Aberrant expression of microRNA‑29a (miR‑29a) has been found in many types of cancers, but not including RB. Therefore, the aims of the present study were to evaluate the regulatory role and underlying mechanism of miR‑29a in human RB. In the present study, we found that miR‑29a expression was significantly downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…miRNAs may act as tumour suppressors or oncogenes, in which aberrantly downregulated miRNAs play tumour-suppressive roles, whereas highly expressed miRNAs serve oncogenic roles in carcinogenesis and cancer progression (12). Emerging studies have indicated that numerous miRNAs are dysregulated in RB, such as miR-29a (13), miR-320 (14), miR-613 (15) and miR-143 (16). Aberrantly expressed miRNAs are closely related with RB formation and progression by regulating various pathological behaviours, such as cellular proliferation, apoptosis, invasion, metastasis and angiogenesis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs may act as tumour suppressors or oncogenes, in which aberrantly downregulated miRNAs play tumour-suppressive roles, whereas highly expressed miRNAs serve oncogenic roles in carcinogenesis and cancer progression (12). Emerging studies have indicated that numerous miRNAs are dysregulated in RB, such as miR-29a (13), miR-320 (14), miR-613 (15) and miR-143 (16). Aberrantly expressed miRNAs are closely related with RB formation and progression by regulating various pathological behaviours, such as cellular proliferation, apoptosis, invasion, metastasis and angiogenesis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have demonstrated that miRNAs are involved in a variety of physiological processes, including cell proliferation, development, survival and differentiation (7)(8)(9)(10). Accumulating studies have also indicated that miRNAs may serve as oncogenes or tumor suppressors to regulate tumor cell proliferation, migration and invasion (11)(12)(13)(14). For instance, miRNA-320a inhibits tumor proliferation and invasion by targeting c-Myc in human hepatocellular carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miRNA-320a inhibits tumor proliferation and invasion by targeting c-Myc in human hepatocellular carcinoma (15). Numerous miRNAs have been reported to regulate the progression of RB, including miR-29a (12), miR106b (13), miRNA-382 (16) and miRNA-320 (17); however, the functions of miRNAs in RB are yet to be determined and the roles of most miRNAs in RB remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, studies have revealed that miRNAs are altered in nearly all human cancer types, and that their alteration contributes toward the initiation and progression of cancer (10)(11)(12). An increasing volume of evidence has recently indicated that numerous miRNAs, including miR-29a (13), miR-138 (14), miR-498 (15) and miR-655 (16), are aberrantly expressed in RB. miRNA dysregulation participates in the regulation of various biological behaviours, including cellular proliferation, cycle, apoptosis and invasion, as well as metastasis and angiogenesis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%